Management of peripheral ossifying fibroma due to severe periodontitis: Case report - Zisis Stefanos; Zisi Vasileios; Shinas Nikolaos; Poulopoulos Konstantinos; Charisi Christina; Papadopoulos Petros; Kyriakou Nikolaos; Cordahi Joe; Anagnostou Eleftherios; Poulopoulos Athanasios (Balkan Journal of Dental Medicine)
Background/Aim: Peripheral ossifying fibroma (POF) constitutes a common reactive lesion of the gingiva, most commonly localized in the anterior maxillary region. Non-neoplastic, originates from the periodontal ligament in response to chronically injurious factors related to periodontal tissues, such as dental calculus, plaque, and orthodontic appliances. The aim of this case report is to illustrate the emergence of the POF in a 46-year-old female patient with severe generalized periodontitis. Case Report: A 46-year-old female patient came to our clinic, complaining of the presence of a rubbery mass in the upper jaw. The clinical examination revealed a pedunculated tumor, with normal color, slightly hard in palpation and with slightly whitish borders. The attachment of this mass to the underlying oral mucosa was relatively stiff but, with some effort, it was observed that the base of this mass is in direct association with the pocket of the tooth #26. At the site of the tumor, the submarginal incision was made with a No. 15C blade at the mesial papilla of tooth #24 following the gingival contour to the distal papilla of #26. It was an alveolar bone-deep incision and planned to remove the entire lesion. The biopsy confirmed the clinical diagnosis of the POF. Conclusions: The diagnosis of the POF may be proven difficult due to its clinical and histological features, resembling other clinical entities, both benign and malignant. Regardless of the possible benign clinical appearance, the tissue should always be examined histologically to confirm the diagnosis. In our case, the absence of medical problems in addition to the presence of periodontitis rendered the diagnostic process simpler. POF commonly originates from the periodontal ligament. The periodontal treatment removes the calculus and the inflammatory stimulus to the periodontal ligament, from the equation. Subsequently, periodontal treatment prevents the recurrence of POF.